2006
DOI: 10.1111/j.1528-1167.2006.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Lateralization in Temporal Lobe Epilepsy: A Comparison between fMRI and the Wada Test

Abstract: Summary:Purpose: Recent studies have claimed that language functional magnetic resonance imaging (f MRI) can identify language lateralization in patients with temporal lobe epilepsy (TLE) and that f MRI-based findings are highly concordant with the conventional assessment procedure of speech dominance, the intracarotid amobarbital test (IAT).Methods: To establish the power of language f MRI to detect language lateralization during presurgical assessment, we compared the findings of a semantic decision paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 59 publications
3
77
0
Order By: Relevance
“…In general, frontal regions show a higher correlation with Wada results than temporal areas [Benke et al, 2006;Lehéricy et al, 2000]. However, it has been suggested that left inferior frontal activation during semantic language paradigms may not be due to language processes in the narrow sense, but rather due to retrieval, selection and evaluation in the semantic executive system [Poldrack et al, 1999].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In general, frontal regions show a higher correlation with Wada results than temporal areas [Benke et al, 2006;Lehéricy et al, 2000]. However, it has been suggested that left inferior frontal activation during semantic language paradigms may not be due to language processes in the narrow sense, but rather due to retrieval, selection and evaluation in the semantic executive system [Poldrack et al, 1999].…”
Section: Discussionmentioning
confidence: 93%
“…All LIs in the left dominant subjects were positive, and all LIs in the right dominant subjects were negative (see Supplementary Table I for an overview of all subjects). Moreover, to test whether mixed speech dominance was present [i.e., divergent lateralization within prefrontal, Broca's, and Wernicke's areas; Benke et al, 2006;Ries et al, 2004;Rutten et al, 2002], we calculated correlation coefficients between the LIs in the three regions both in the sample investigated in our study and in a more extended group of 132 healthy subjects. We found that for both groups, LIs were highly correlated (group of 32 subjects from the current study: Broca-Wernicke: Spearman's correlation coefficient R 5 0.682; P < 10…”
Section: Behavioral Data and Language Dominancementioning
confidence: 99%
“…Although this modality has been a gold standard for lateralizing language hemispheres, the major drawback of the Wada test is that it is invasive with inherent risks 1) . Many studies have shown that fMRI is at least comparable to the Wada test in terms of lateralizing language function 5,6,12,25) . Thus, fMRI appears to be a promising modality for the evaluation of language function, especially in terms of preoperative planning in order to preserve essential language areas.…”
Section: Overviewmentioning
confidence: 99%
“…Various modalities, such as the Wada test, fMRI, functional PET, and magnetoencephalography, can be used for non-invasive localization or lateralization of language area(s) for presurgical purposes. The Wada test and fMRI are the most popular of these modalities 5,6,12,24) . Although the Wada test can serve as a useful index of language laterality, it is less useful for localizing language areas.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation